Liver tryptase-positive mast cells and fibrosis in children with hepatic echinococcosis - Gulubova Maya; Vlaykova Tatyana; Kalinova Krasimira; Vodenicharov Angel; Vasilev Ivan; Velev Valentin (Wolters Kluwer Medknow Publications, 2005)
The hepatic echinococcosis in children is a serious surgical problem. The aim of this study is to investigate the participation of mast cells in liver inflammatory reactions triggered by echinococcal cysts. Liver biopsy samples were collected from the tissue surrounding the cysts from 16 sick children (11 boys and 5 girls) in the course of abdominal surgery and from 5 controls. Light and ultrastructural immunocytochemistry was performed using monoclonal antibody against tryptase. Light microscopical immunocytochemistry revealed abundance of tryptase-positive (MCT) mast cells in the capsules of the cysts (43.58 cells/mm2). There were also observed greatly increased numbers of mast cells in portal tracts surrounding the cyst, compared to those of control biopsies (26.49 vs. 1.78 cells/mm2, p=0.0009, Mann-Whitney U test). Based on the ultrastructural appearance of tryptase-positive mast cell granules, morphological sings of activation of most of the mast cells were distinguished. In conclusion, we suggest that the accumulated and activated tryptase-positive mast cells in liver tissues surrounding the echinococcal cysts play a crucial role in modulation of the inflammatory liver response and could induce chronic inflammation and fibrogenesis, resulting in serious liver injury such as nonspecific reactive hepatitis.